مقدمات’ بوطیقا ‘(اردو)کا تنقیدی مطالعہ: Critical Study of Prefaces (Urdu) of Poetics - Ejaz, Dr. Sumaira (Zoraiz, 2024)
‘Poetics’ holds the ultimate remarkable status in the global context of literary criticism. Even after two thousand years, the debates on determining the standards of poetry are a tribute to this book. It has been translated into every major language of the world. In Urdu, the series of its translations have been started in 1941. The special thing about these translations is their prefaces. Among these preface writers, the names of Aziz Ahmad, Jameel Jalibi, Muhammad Yasin and Shams ur Rahman Farooqi are included. In addition to highlighting its importance ,its post effects have also been highlighted in comparison with the literature of other languages of the world .In this article, the major critical trends of ‘Poetics’ and characteristics of these prefaces are being reviewed.